The Psychiatric-Religious Condition of Educated Homosexual Community In Islamic Campus - Azam Syukur Rahmatullah (Politeknik Negeri Bali, 2020)
This research reveals the spiritual-psychological conditions of homosexual students on the Islamic campus of Yogyakarta, Indonesia. The researcher had interviewed four homosexuals from two Islamic based campuses in Yogyakarta. Two respondents came from the Islamic campus A, both of them worshiped, and two respondents were from the Islamic campus B, the two respondents also worshiped. The results of the study stated that these four homosexuals experienced the hesitation of religious spirit, in which one side they continued to carry out Islamic-based campus rules such as prayer, fasting, reading the Qur'an, halaqah, Islamic studies on campus, but on the other hand, the homosexual soul possessed is not easily removed. In the end, they experience